Trust Breeds Trust: How Taxpayers are Treated - Lars P. Feld; Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2000)
Tax compliance has been studied in economics by analysing the individual decision of a representative person between paying and evading taxes. A neglected aspect of tax compliance is the interaction of taxpayers and tax authorities. The relationship between the two actors can be understood as an implicit or psychological contract. The more strongly the political participation rights are developed, the more important this contract is, and the higher tax morale is. In this paper, empirical evidence based on a survey of tax authorities of the 26 Swiss states (cantons) is presented, indicating that the differences in the treatment of taxpayers by tax authorities can be explained by differences in political participation rights.
Keywords: 330; Tax evasion; tax authority; tax compliance; direct democracy